Pengembangan Instrumen Asesmen Kompetensi Minimum Fisika SMA - Novika, Resti (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
This study aims to produce a minimum competency assessment instrument for high school physics. The purpose of this study was to determine the quality of the minimum high school physics competency assessment instrument (AKMPhys). This research is research and development research. Selection of test subjects using purposive sampling. This research and development resulted in the quality of the AKMPhys instrument in terms of content validity, the Aiken's V score was in the valid category. The empirical validity based on item compatibility with the IRT Rasch model and PCM approach proved that 80 items fit the model. Reliability estimation based on Cronbach's Alpha reliability is obtained with very reliable criteria. The item difficulty level is in the range of -3.5 to 2.9.